Demokrasi di Malaysia - Abdul Rahman Aziz (Kuala Lumpur : Institut Terjemahan & Buku Malaysia, 2014)
On history of political science on democracy and leadership in Malaysia.
Keywords: Democracy -- Malaysia; Leadership -- Malaysia; Malaysia -- Politics and government